Endogenous Type I CRISPR-Cas: From Foreign DNA Defense to Prokaryotic Engineering - Zheng, Yanli; Li, Jie; Wang, Baiyang; Han, Jiamei; Hao, Yile; Wang, Shengchen; Ma, Xiangdong; Yang, Shihui; Ma, Lixin; Yi, Li; Peng, Wenfang (Frontiers in Bioengineering and Biotechnology, 2020)
Establishment of production platforms through prokaryotic engineering in microbial organisms would be one of the most efficient means for chemicals, protein, and biofuels production. Despite the fact that CRISPR (clustered regularly interspaced short palindromic repeats)–based technologies have readily emerged as powerful and versatile tools for genetic manipulations, their applications are generally limited in prokaryotes, possibly owing to the large size and severe cytotoxicity of the heterogeneous Cas (CRISPR-associated) effector. Nevertheless, the rich natural occurrence of CRISPR-Cas systems in many bacteria and most archaea holds great potential for endogenous CRISPR-based prokaryotic engineering. The endogenous CRISPR-Cas systems, with type I systems that constitute the most abundant and diverse group, would be repurposed as genetic manipulation tools once they are identified and characterized as functional in their native hosts. This article reviews the major progress made in understanding the mechanisms of invading DNA immunity by type I CRISPR-Cas and summarizes the practical applications of endogenous type I CRISPR-based toolkits for prokaryotic engineering.